ANALISIS HUKUM PERUSAHAAN PEMEGANG SERTIFIKAT JAMINAN FIDUSIA DALAM MELAKUKAN UPAYA HUKUM TERHADAP DEBITUR YANG INGKAR JANJI - Ade Darmawan Basri (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2022)
Abstract The purpose of conducting this research is to find out the legal relationship of finance companies in fiduciary guarantees and how the position of creditors is regarding fiduciary guarantee objects that are charged to customers/debtors. The method used is normative juridical, the legal materials used in this research are primary legal materials and secondary legal materials. As is known, it is often found that objects are burdened with fiduciary guarantees or are fiduciary more than once. This is done by the company in order to obtain loans from other creditors so that needs can be met. However, the fact that occurs in the field is that finance companies suffer a lot of losses due to the negligence of the debtor or the customer himself who reneges on the agreement and in the process of returning the vehicle unit in the hands of the debtor it is difficult to execute and even though using a fiduciary guarantee certificate there are still debtors who deny what has been agreed upon and agreed upon between the company and the debtor himself. Which then actually by placing a fiduciary guarantee certificate can guarantee creditors or the company in executing units from debtors who have broken promises or defaults. Keywords: Fiduciary Guarantee, Financing Company, Leasing.